2015
DOI: 10.1371/journal.pone.0134927
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Ablation of CD38 Protects against Western Diet-Induced Exercise Intolerance and Metabolic Inflexibility

Abstract: Nicotinamide adenine dinucleotide (NAD+) is a key cofactor required for essential metabolic oxidation-reduction reactions. It also regulates various cellular activities, including gene expression, signaling, DNA repair and calcium homeostasis. Intracellular NAD+ levels are tightly regulated and often respond rapidly to nutritional and environmental changes. Numerous studies indicate that elevating NAD+ may be therapeutically beneficial in the context of numerous diseases. However, the role of NAD+ on skeletal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
35
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(38 citation statements)
references
References 35 publications
3
35
0
Order By: Relevance
“…Thus, CD38 and BST-1 may have an important impact on the regulation of cellular metabolism and signaling, including regulation of the activity of SIRTUINS (Aksoy et al, 2006b; Barbosa et al, 2007). In fact, we and others have previously shown that CD38 regulates the organismal response to high caloric feeding and that genetic or pharmacological ablation of CD38 protects against high fat diet-induced metabolic dysfunction via modulation of SIRT1 activity (Barbosa et al, 2007; Chiang et al, 2015). …”
Section: Mechanisms Of Nad Catabolismmentioning
confidence: 94%
See 1 more Smart Citation
“…Thus, CD38 and BST-1 may have an important impact on the regulation of cellular metabolism and signaling, including regulation of the activity of SIRTUINS (Aksoy et al, 2006b; Barbosa et al, 2007). In fact, we and others have previously shown that CD38 regulates the organismal response to high caloric feeding and that genetic or pharmacological ablation of CD38 protects against high fat diet-induced metabolic dysfunction via modulation of SIRT1 activity (Barbosa et al, 2007; Chiang et al, 2015). …”
Section: Mechanisms Of Nad Catabolismmentioning
confidence: 94%
“…In addition, NADase activity was almost absent in CD38 knockout mice (Aksoy et al, 2006a; Young et al, 2006), suggesting that CD38 is the main NADase in mammalian tissues. We and others have previously shown that CD38 knockout mice have higher NAD levels and are protected against obesity and metabolic syndrome (Barbosa et al, 2007; Chiang et al, 2015). In addition, treatment of obese mice with CD38 inhibitors increased intracellular NAD levels and improved several aspects of glucose and lipid homeostasis (Escande et al, 2013; Haffner et al, 2015).…”
Section: What Causes the Nad Decline Observed During The Aging Process?mentioning
confidence: 97%
“…For example, cells overexpressing CD38 showed decreased [NAD ϩ ] together with decreased expression of antioxidant proteins, likely due to reduced sirtuin activity (391). As an effect of this metabolism, CD38 knockout mice showed improved resistance to glucose intolerance and diet-induced obesity (392,393). This correlated with increased [NAD ϩ ] in multiple tissues and increased sirtuin activity (392,394).…”
Section: Parp Nad ؉ Metabolism and Inflammationmentioning
confidence: 99%
“…Similar to PARPs, alterations in the content of CD38 tightly correlate with changes in NAD + levels, with CD38 deletion leading to marked increases in NAD + and CD38 overexpression and causing reduced NAD + concentrations . Deletion of CD38 raises NAD + levels substantially in mice and protects from diet‐induced obesity, metabolic inflexibility, fatty liver and glucose intolerance . Similarly the flavonoid apigenin was recently described as a CD38 inhibitor, and administration in obese mice increased NAD + levels and improved glucose and lipid homeostasis .…”
Section: Nad+ Levels Are Dynamic and Correlate With Metabolic Statusmentioning
confidence: 94%
“…[49][50][51] Deletion of CD38 raises NAD + levels substantially in mice and protects from diet-induced obesity, metabolic inflexibility, fatty liver and glucose intolerance. 50,52 Similarly the flavonoid apigenin was recently described as a CD38 inhibitor, and administration in obese mice increased NAD + levels and improved glucose and lipid homeostasis. 53 More potent inhibitors of CD38 have recently been described and, although they produce marked increases in tissue NAD + levels, their effect on metabolic parameters has not yet been determined.…”
Section: Nad + Levels Are Dynamic and Correlate With Metabolic Statusmentioning
confidence: 99%